Oxidation behaviour of NiCoCrAlYHfZr coating on a fourth generation single crystal superalloy. (15th July 2021) - Liu, S.B.; Li, W.; Fu, L.B.; Wang, T.G.; Jiang, S.M.; Gong, J.; Sun, C.
Highlights: The NiCoCrAlY coating and NiCoCrAlYHfZr coating were prepared on a fourth generation single crystal superalloy by arc ion plating. The NiCoCrAlYHfZr coating shows enhanced oxidation resistance and improved scale adhesion. The addition of Hf and Zr in the coating inhibited the the formation of large voids. The NiCoCrAlYHfZr coating has less effect on the substrate and less TCP phases can be found in the SRZ. Abstract: The NiCoCrAlY coating and NiCoCrAlYHfZr coating were prepared on a fourth generation single crystal superalloy by arc ion plating. The cyclic and isothermal oxidation behaviours of the two coatings were both investigated in static laboratory air. Numerous large voids were formed in the oxide scale of NiCoCrAlY coating and they were responsible for the scale spallation. While the NiCoCrAlYHfZr coating showed better oxidation performance due to the enhanced scale adhesion. The advantage of Hf and Zr addition in the coating were discussed as well as the mutual diffusion behaviour between the coating and the substrate.